Detection of wind turbines rotary motion by birds: A matter of speed and contrast - Constance Blary; Francesco Bonadonna; Elise Dussauze; Simon Potier; Aurélien Besnard; Olivier Duriez (Conservation Science and Practice, 2023)
Abstract To reduce bird collisions on wind turbines, Automatic Detection Systems have been developed to locate approaching birds and trigger turbines to slowdown to 2–3 rotations per minute (rpm). However, it is unknown whether birds can detect this reduced speed and avoid the turbine. We conducted an operant conditioning experiment on domestic doves (Streptopelia roseogrisea) and Harris's hawks (Parabuteo unicinctus) to assess their ability to discriminate between stationary and rotating miniature wind turbines, depending on the rotation speed and the contrast between the white blades and the background (only for doves for the latter). At high contrast, regardless of the speed tested, hawks were able to differentiate between the rotating and stationary turbines, while doves were not able to discriminate the slow‐rotating turbine (3 rpm) from the stationary one. The discrimination threshold increased to 8 rpm for the doves when the contrast was reduced. Our results suggest that the residual wind turbine speed of 2–3 rpm may not be detected by all bird species under all environmental conditions. Increasing the contrast between wind turbines and their environment may improve the detection of low‐speed rotation by some birds, otherwise, complete turbine shutdown should be recommended.